Modulating Alginate Hydrogels for Improved Biological Performance as Cellular 3D Microenvironments - Neves, Mariana Isabel; Moroni, Lorenzo; Barrias, Cristina Carvalho (Frontiers in Bioengineering and Biotechnology, 2020)
For biomedical applications, the choice and design of biomaterials is crucial for successful in vitro and in vivo strategies, ultimately affecting their potential clinical application and performance. Alginate, a marine-derived polysaccharide obtained from seaweeds, is one of the most widely used polymers in the biomedical field, particularly to build three dimensional (3D) systems for culture and delivery of cells. Despite its biocompatibility, alginate hydrogels require modifications to improve their biological activity, namely inclusion of mammalian cell-interactive domains and fine-tuning of mechanical properties. These chemical modifications enable the addition of new features for greater versatility and control over alginate-based systems, extending the plethora of applications and procedures where they can be used. This review provides an overview on alginate properties and current clinical applications, along with different strategies developed to improve alginate hydrogels performance as 3D scaffolds and 4D dynamic systems.